PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR OLEH DOSEN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI JAKARTA - Diana Ariani (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
The purpose of this research is to describe how the lectures of the School of Education in State University of Jakarta use internet as a learning resource. The population covered all lecturers of the School of Education and respondents were selective by proporsional random sampling technique. The data were collected by using questioner and interviewing. The result of the research shows that most of the lecturers have utilized internet for their own interest but not for instructional purposes in the classroom. Very few of the respondents indicate that they are not familiar with internet. The problems in using internet as a learning resource include the limited knowledge of the lecturers in using internet for instructional purposes and limited facility available in the School of Education. This research suggests the School of Education encourages all the lecturers to take benefit of internet as learning resources in each course and it is an urgent need to provide enough facility to access internet for all of lectures.